Development of a Traditional Dam-Daman Game Based Physical Education Model to Enhance Learning Motivation among Junior High School Students in Musi Rawas, Indonesia - Abdul Aziz; Putri Cicilia Kristina; Bambang Hermansah (Jurnal Porkes, 2026)
Low learning motivation in Physical Education, Sport, and Health (PESH) remains a persistent challenge at the junior high school level, particularly in schools with limited access to innovative instructional models. This study aims to: (1) develop a valid Dam-Daman traditional game–based PESH learning model, (2) test its practicality, and (3) identify its effect on students' learning motivation. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) combined with Tessmer's formative evaluation. Product trials involved expert validation (n=3), one-to-one testing (n=3), small group testing (n=6), and a field test with pretest-posttest design (n=23 students) at SMP Ma'arif NU Tugumulyo, Musi Rawas Regency. Data were analyzed using descriptive statistics (mean, SD, percentage) and inferential statistics (Shapiro-Wilk normality test, paired sample t-test, N-gain, and Cohen's d effect size). Expert validation results showed high validity for learning design (M=4.9, SD=0.18), material/content (M=3.9, SD=0.32), and media (M=4.3, SD=0.27). Practicality was very high in one-to-one (M=4.5, SD=0.35) and small group stages (M=4.3, SD=0.41). The field test revealed a significant increase in motivation from pretest (79, 56.4%) to posttest (119, 85.0%) with t (22)=12.347, p=0.000, N-gain=0.66 (moderate effectiveness), and Cohen's d=4.87 (large effect). The findings align with Keller's ARCS motivation model and Vygotsky's play theory, demonstrating that cultural relevance, game-based structure, and systematic development contribute to the model's effectiveness. However, limitations include the absence of a control group and single-school setting. In conclusion, the Dam-Daman game–based PESH learning model is valid, highly practical, and has a statistically significant large effect on junior high school students' learning motivation. This model is recommended as a contextual and enjoyable alternative for PESH instruction.